Administration of garlic and neem in broiler diet for safe meat production (Bangladesh Journal of Animal Science, 2020)
This study was conducted to observe the effect of different administration method of garlic and neem on growth performances, feed efficiency and serum biochemical parameters for safe broiler production. The experiment was done for a period of 32 days with 384 one-day-old straight run broiler chicks. The broiler chicks were divided into six groups each of 64 birds and replicated to four subgroups each of 16 birds. The dietary groups were; control (basal diet; no additives), antibiotic (basal diet + antibiotic), garlic in feed (basal diet + 0.25% garlic powder), garlic in water (basal diet + garlic extracts), neem in feed (basal diet + 0.25% neem powder) and neem in water (basal diet + neem extracts). Results showed that the body weight and body weight gain increased significantly (P0.05) among the treatment groups. Garlic in feed and water and neem in feed groups showed better FCR (P0.05) difference in meat yield, bone development and dressing parameters except head and gizzard in different dietary groups. Supplementation of garlic with feed and water significantly (P0.05) differences in serum glucose and GPT among different treatment groups. GOT was significantly (P